Impact of cancer diagnosis on different aspects of life of patients of cancer breast and cancer cervix uteri: a cross sectional study at Government Medical College, Amritsar, Punjab - Khullar, Nandika; Singh, Tejbir; Lal, Mohan; Kaur, Jasleen (International Journal Of Community Medicine And Public Health, 2018)
Background: Advancements in understanding about the etiology and pathogenesis of cancer has led to increased awareness regarding the clinical course of disease and its appropriate treatments. This is the major reason behind longer life expectancy in cancer patients. However, this longer life is not necessarily an easy one due to debilitating nature of both the disease and its treatment modalities. This study was done to assess the impact of cancer diagnosis on the psycho-social aspects of patient’s lives. Methods: All patients of cancer breast and cancer of cervix uteri, who reported between January 1, 2013 to December 31, 2015; at Radiotherapy Department, Guru Nanak Dev Hospital, Government Medical College, Amritsar and were residents of Amritsar District, were listed and a total of 127 patients were included in the study. Patients were interviewed using a pre-tested, pre-designed questionnaire at their place of residence. Results: Assessing the demands of the altered lives of cancer patients in different aspects like modifications in daily living, loss of work and pleasure, reformed religious/spiritual opinions, social support received etc. It is seen that social life of patients is affected after diagnosis of cancer. However, social support received by the patients and families is similar as compared to before diagnosis. Conclusions:Maximal impact of cancer, its diagnosis and treatment is on various aspects of the life of patients not only immediate family but relatives, friends and neighbours lend psychological, social and economic support in such situations which helps a cancer survivor cope with the trauma and carry on with their lives.